Measuring Disability in Consumers of mental health services – psychometric properties of the World Health Organization Disability Assessment Schedule 2.0 (WHODAS 2.0) in Ghana. (21st July 2021) - Badu, Eric; Mitchell, Rebecca; O'Brien, Anthony Paul; Osei, Akwasi; Rubin, Mark
Abstract: The World Health Disability Assessment Scale (WHODAS‐2.0) has widely been accepted as the standard measure of disability. However, psychometric testing is mostly performed in developed countries. This paper aims to assess the psychometric properties (reliability, validity) of the WHODAS‐2.0 among consumers of mental health services in Ghana. Two translators (expert in English language and Akan language) performed forward and backward translation of the WHODAS‐2.0 from English language to Ghanaian language (Twi). A total of 510 consumers of mental health services were recruited consecutively to complete the WHODAS‐2.0 using RedCAP. Confirmatory factor analysis was used to analyse the data. All domains in the 6‐factor solutions had excellent internal consistency (ω = 0.90–0.98), sufficient convergent validity and had satisfactory discriminant validity except for domain on participation. The CFA model confirmed that the data had a good model fit, CFI = 0.97, TLI = 0.96, RMESA = 0.05, RMR = 0.03; NFI = 0.94; χ 2  = 1243.8, df = 529, P  < 0.001. Although the WHODAS 2.0 had satisfactory psychometric properties and was thus considered to be a reliable and valid measure for assessing disability and level of functioning in consumers of mental health services, researchers and clinicians should re‐consider items within the participation domain. Also, practitioners are encouraged to integrate the WHODAS‐2.0 into the collection of data on clinical outcomes, as well as, collecting data on government social protection intervention programmes for consumers.